2022
DOI: 10.3389/fimmu.2022.1054445
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics to identify potential key biomarkers for COVID-19-related chronic urticaria

Abstract: BackgroundA lot of studies have revealed that chronic urticaria (CU) is closely linked with COVID-19. However, there is a lack of further study at the gene level. This research is aimed to investigate the molecular mechanism of COVID-19-related CU via bioinformatic ways.MethodsThe RNA expression profile datasets of CU (GSE72540) and COVID-19 (GSE164805) were used for the training data and GSE57178 for the verification data. After recognizing the shared differently expressed genes (DEGs) of COVID-19 and CU, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The current study showed that CXCL1, CCL2, CCL3, CXCL6, CCL4, and CXCL2 chemokines play important roles in the occurrence of skin manifestation. In the study by Zhang et al, it was found that increased production of CCL3 and CCL4 in COVID-19 patients caused chronic urticarial (45). Moreover, in the study of Rybkina et al, CCL3 and CCL4 produced by cytokine storms cause the progression of skin lesions (46).…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that CXCL1, CCL2, CCL3, CXCL6, CCL4, and CXCL2 chemokines play important roles in the occurrence of skin manifestation. In the study by Zhang et al, it was found that increased production of CCL3 and CCL4 in COVID-19 patients caused chronic urticarial (45). Moreover, in the study of Rybkina et al, CCL3 and CCL4 produced by cytokine storms cause the progression of skin lesions (46).…”
Section: Discussionmentioning
confidence: 99%
“…PCA and boxplot analyses demonstrated the effectiveness of the merged dataset in subsequent analyses. GSE57178 and GSE72540 were individually utilized in previous studies ( 25 , 26 ). However, our dataset merging approach increased the sample size and enhanced reproducibility and data integration.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic urticaria (CU) is a dermatological condition that manifests as an angioedema or wheal for more than 42 days. 1 It is a chronic pruritus condition with a global prevalence of about 1.8%, steadily rising during the coronavirus 2019 (COVID‐19) pandemic period. 2 , 3 CU affects the quality of life of individuals and leads to financial burdens on families seeking medical care and treatment.…”
Section: Introductionmentioning
confidence: 99%